CRIMINAL LEGISLATION REGARDING CRIMES AGAINST SEXUAL FREEDOM AND INTEGRITY COMMITTED AGAINST MINORS - Buneci, Petre (International Journal of Legal and Social Order, 2024)
This study analyzes the criminal legislation in Romania regarding crimes against sexual freedom and integrity committed against minors, in the context of the recent amendments to the Criminal Code of 2023 and 2024. Despite efforts to align with European directives and strengthen the protection of minors, frequent changes and inconsistencies of legislation challenge effective law enforcement. The rapid succession of changes and legal ambiguities can affect the real protection of minors. In our opinion a coherent penal policy and the adoption of clear measures to protect the rights of minors, in accordance with international standards, are necessary.